2018
DOI: 10.4314/jfas.v9i4s.26
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian sign language dataset for automatic sign language recognition system

Abstract: Hearing impaired individuals have issues to communicate with normal people. They have their own language called Sign Language (SL) to express their feeling or to communi with others. As communication is an essential part of normal everyday life, it is particularly important for deaf people to communicate as normally as possible with others. Recent advancements in computing technologies have the potential to be applied recognition. These computer language and vice-versa. This paper describes the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…They trained the network with a learning rate of 0.05 using 225 samples and achieved 80.54% accuracy on 15 dynamic signs. In 2017, Karbasi, Zabidi, Yassin, Waqas, and Bhatti [27] demonstrated a dataset development for MSL consisting of alphabets and ten (10) dynamic signs using Microsoft Kinect.…”
Section: Relevant Past Studies On Malaysian Sign Languagementioning
confidence: 99%
“…They trained the network with a learning rate of 0.05 using 225 samples and achieved 80.54% accuracy on 15 dynamic signs. In 2017, Karbasi, Zabidi, Yassin, Waqas, and Bhatti [27] demonstrated a dataset development for MSL consisting of alphabets and ten (10) dynamic signs using Microsoft Kinect.…”
Section: Relevant Past Studies On Malaysian Sign Languagementioning
confidence: 99%
“…They trained the network with a learning rate of 0.05 using 225 samples and achieved 80.54% accuracy on 15 dynamic signs. In 2017, Karbasi et al [ 30 ] demonstrated a dataset development for MSL consisting of alphabets and ten (10) dynamic signs using Microsoft Kinect. In 2019, Fahmi et al [ 31 ] proposed a hand signs translator system based on the fuzzy logic method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Communication is a tedious task for people who have hearing and speech impairments. Hand gestures, which involve the movement of hands, are used as sign language for natural communication between ordinary people and deaf people, which is just like speech for vocal people [4,[6][7][8][9]. Nonetheless, sign languages differ by country and are used for a variety of purposes, including American Sign Language (ASL), British Sign Language (BSL), Japanese Sign Language [10,11], and Turkish Sign Language (TSL) [12].…”
Section: Introductionmentioning
confidence: 99%